Using Small Group Debates to Actively Engage Students in an Introductory Microbiology Course - Joyce A. Shaw (Journal of Microbiology & Biology Education, 2012)
Debates stimulate critical thinking and can be a highly effective way to actively engage students in the classroom. This paper describes a small group debate format in which groups of four to six students debated preassigned topics in microbiology in front of the rest of the class. Rapid advancements in science, especially in microbiology, provide the scaffolding for students to locate and share evidence-based information from a plethora of complex and often conflicting sources. Student-generated debate presentations can be a welcome respite from the lecture format. Debates were scheduled throughout the course to coincide with topics being covered. Questionnaires distributed immediately after each debate revealed that the debates were well received by students and were effective in changing student attitudes and misconceptions. Debate preparation provided students the opportunity to gain proficiency in accessing information from electronic databases, to use resources from professional organizations, and to synthesize and analyze information. In addition, the debate process gave students experience in developing oral communication skills.